questions in the pic
Attachments:
![](https://hi-static.z-dn.net/files/d2b/708203c6cc014b011038efada71e7731.jpg)
Answers
Answered by
0
ax + by = a - b
bx - ay = a + b
Multiply equation 1 by a and equation 2 by b
a²x + aby = a² - ab
b²x - aby = ab + b²
Adding them
(a² + b²) x = (a² + b²)
x = 1
Now put x = 1 in equation 1, then y = -1
So, (1,-1) is the solution
bx - ay = a + b
Multiply equation 1 by a and equation 2 by b
a²x + aby = a² - ab
b²x - aby = ab + b²
Adding them
(a² + b²) x = (a² + b²)
x = 1
Now put x = 1 in equation 1, then y = -1
So, (1,-1) is the solution
Answered by
0
hi,
hope it helps.
.......
hope it helps.
.......
Attachments:
![](https://hi-static.z-dn.net/files/db5/8adb22286e8c055ce0184d08e5f6d41c.jpg)
Similar questions
Physics,
8 months ago
India Languages,
8 months ago
Computer Science,
1 year ago
Math,
1 year ago
English,
1 year ago
Biology,
1 year ago
Chemistry,
1 year ago